Pengaruh SMM dan E-Wom Terhadap Visit Intention dengan Destination Image Sebagai Variabel Intervening pada Industri Pariwisata Religi: Studi Kasus Syeikh Zayed Grand Mosque Solo - Anggi Angellia; Ahmad Mardalis (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Tourism has the capacity to significantly contribute to Indonesia's economic expansion by creating employment opportunities and enhancing the country's infrastructure. Nonetheless, in the current digital age, promoting visitor destinations presents the tourism industry with new obstacles. Tourism industry participants are required to implement effective promotional strategies for their respective tourist destinations to pique the interest of prospective visitors. This study used the destination picture as a mediating variable to investigate the effects of SMM and E-WOM on visit intention. In this study, 340 users of social networking sites made up the study sample. In this experiment, purposive sampling combined with a non-probability sampling approach was used. A questionnaire was used to gather information from original sources. Smart PLS was used to help in data analysis. The study's findings indicate that people's impressions of a place and their trip plans are directly influenced by SMM and E-WOM. Furthermore, a person's opinion of a location has a big impact on how likely they are to visit there. The mediation test results showed that the association between SMM, E-WOM, and visit intention is mediated by destination image.